STUDY INTERACTION OF GROUNDWATER â SURFAACE WATER OF CISANGKUY WATERHED BY COUPLED SWAT â MODFLOW METHOD - Husna, Abdullah
A comprehensive understanding of the characteristics of hydrologicalhydrogeological interactions can be done using modeling. Previous studies conducted simulations of ground-surface water separately, whereas groundwater and surface water had a direct impact on each other in terms of quantity and quality. This study aimed to evaluate the ability of the SWAT-MODFLOW coupled model applied in the Cisangkuy watershed area, Bandung Regency to understand the characteristics of river catchments in the area. The input data of this model is digital elevation model, river network map, land use map, soil type map, and climatology data. The results of the SWAT-MODFLOW simulation can show the recharge and discharge patterns in river segments, as well as the quantification of groundwater and surface water conditions in the study area. This research consists of several stages, namely the construction of the SWAT model, the construction of the MODFLOW model, and the integration of SWAT - MODFLOW. Furthermore, the model was calibrated with the SUFI-2 algorithm.